2018
DOI: 10.1371/journal.pone.0190856
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence (IPV): The validity of an IPV screening instrument utilized among pregnant women in Tanzania and Vietnam

Abstract: BackgroundIntimate partner violence (IPV) is a global problem that affects one-third of all women. The present study aims to develop and determine the validity of a screening instrument for the detection of IPV in pregnant women in Tanzania and Vietnam and to determine the minimum number of questions needed to identify IPV.MethodAn IPV screening instrument based on eight questions was tested on 1,116 Tanzanian and 1,309 Vietnamese women who attended antenatal care before 24 gestational weeks. The women were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
(23 reference statements)
3
10
0
Order By: Relevance
“…Apart from the DHS, there are few other studies in Uganda, but older hospital-based studies record a prevalence of physical IPV in pregnancy similar to our findings 16 17. Other research in SSA found physical IPV in pregnancy rates of 22.5%, 22% and 9% in Nigeria, 10.7% in Tanzania and 36% in South Africa 22–25. Similar studies in other low resource settings such as India (12%) and Bangladesh (35.2%) reveal much lower rates of physical IPV in pregnancy than reported in SSA,26 with the exception of a single study in Bangladesh 27.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from the DHS, there are few other studies in Uganda, but older hospital-based studies record a prevalence of physical IPV in pregnancy similar to our findings 16 17. Other research in SSA found physical IPV in pregnancy rates of 22.5%, 22% and 9% in Nigeria, 10.7% in Tanzania and 36% in South Africa 22–25. Similar studies in other low resource settings such as India (12%) and Bangladesh (35.2%) reveal much lower rates of physical IPV in pregnancy than reported in SSA,26 with the exception of a single study in Bangladesh 27.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, social support was classified into three categories: high social support (scores 24–30), medium social support [ 18 – 23 ], and low social support (below 18) categories [ 21 ]. Intimate partner violence was measured by intimate partner violence scale; intimate partner violence was considered if a pregnant woman reported one of the following during the current pregnancy: husband/partner have done things to scare or intimidate on purpose or threatened to hurt someone they care about or hit, slapped, or thrown something that could hurt her or forced or pressured to have sexual intercourse when she did not want to [ 25 , 26 ]. Obstetric and clinical parameters in this study include pregnancy planning, gravidity, parity, trimester, history of abortion, history of stillbirth, perceived complication during a previous pregnancy, having currently known medical illness, and currently taking medication.…”
Section: Methodsmentioning
confidence: 99%
“…We identified women who were exposed to Intimate Partner Violence (IPV) during pregnancy by asking pregnant women three questions on emotional IPV, physical IPV, and sexual IPV. The presence of IPV was ascertained by the presence of at least one type of IPV [ 61 ].…”
Section: Methodsmentioning
confidence: 99%